Effects of intermittent and continuous calorie restriction on body weight and metabolism over 50 wk: a randomized controlled trial. Issue 5 (23rd November 2018) - Schübel, Ruth; Nattenmüller, Johanna; Sookthai, Disorn; Nonnenmacher, Tobias; Graf, Mirja E; Riedl, Lena; Schlett, Christopher L; von Stackelberg, Oyunbileg; Johnson, Theron; Nabers, Diana; Kirsten, Romy; Kratz, Mario; et al.
ABSTRACT: Background: Although preliminary evidence suggests that intermittent calorie restriction (ICR) exerts stronger effects on metabolic parameters, which may link obesity and major chronic diseases, compared with continuous calorie restriction (CCR), there is a lack of well-powered intervention studies. Objective: We conducted a randomized controlled trial to test whether ICR, operationalized as the "5:2 diet, " has stronger effects on adipose tissue gene expression, anthropometric and body composition measures, and circulating metabolic biomarkers than CCR and a control regimen. Design: One hundred and fifty overweight and obese nonsmokers [body mass index (kg/m 2 ) ≥25 to <40, 50% women], aged 35–65 y, were randomly assigned to an ICR group (5 d without energy restriction and 2 d with 75% energy deficit, net weekly energy deficit ∼20%), a CCR group (daily energy deficit ∼20%), or a control group (no advice to restrict energy) and participated in a 12-wk intervention phase, a 12-wk maintenance phase, and a 26-wk follow-up phase. Results: Loge relative weight change over the intervention phase was −7.1% ± 0.7% (mean ± SEM) with ICR, −5.2% ± 0.6% with CCR, and −3.3% ± 0.6% with the control regimen ( P overall < 0.001, P ICR vs. CCR = 0.053). Despite slightly greater weight loss with ICR than with CCR, there were no significant differences between the groups in the expression of 82 preselected genes in adipose tissue implicated in pathways linking obesity to chronic diseases. At the final follow-up assessment (week 50), weight loss was −5.2% ± 1.2% with ICR, −4.9% ± 1.1% with CCR, and −1.7% ± 0.8% with the control regimen ( P overall = 0.01, P ICR vs. CCR = 0.89). These effects were paralleled by proportional changes in visceral and subcutaneous adipose tissue volumes. There were no significant differences between ICR and CCR regarding various circulating metabolic biomarkers. Conclusion: Our results on the effects of the "5:2 diet" indicate that ICR may be equivalent but not superior to CCR for weight reduction and prevention of metabolic diseases. This trial was registered at clinicaltrials.gov as NCT02449148.